High tree diversity enhances light interception in tropical forests - Duarte, Marina Melo (2021)
Understanding the processes that underlie the effects of tree diversity on primary production is of foremost importance to enhance climate change mitigation by tropical forests. Here, we investigated the effects of tree diversity on light interception over space and time in two tropical tree experiments, located in Panama—Sardinilla site (monocultures to 18-species mixtures), and in Brazil—Anhembi site (20- to 114-species mixtures). We assessed intercepted photosynthetically active radiation (iPAR) over horizontal grids and vertical transects (up to 5 m high in Sardinilla and up to 4 m high in Anhembi), in plots containing different richness levels and combinations of species. Light interception increased from monocultures to 5-species mixtures in Sardinilla and from 20- to 114-species mixtures in Anhembi (during the dry season). At the Sardinilla site, five-species mixtures showed iPAR comparable to the best performing monocultures, despite substantial differences observed among monocultures. Diversity-iPAR relationships changed seasonally and were more pronounced during the dry season. Tree richness promoted a less variable temporal and spatial (i.e. both horizontal and vertical) distribution of light interception. Synthesis. High tree diversity (i.e. over a hundred species in mixture) maximizes the amount of light intercepted by the canopy in restored tropical forests through more even capture in space and time. Diversity-light interception relationships should be critically considered for designing cost-efficient large-scale tropical forest restoration programs.